Model predictive control of an inverted pendulum - Askari, M.; Mohamed, H.A.F.; Moghavvemi, M.; Yang, S.S. (2009)
In this paper, model predictive control is applied to an inverted pendulum apparatus and the effect of input disturbance are studied. The optimization problem is solved on-line using quadratic programming approach on a PC hardware platform.